Human Amniotic Membrane as a Suitable Matrix for Growth of Mouse Urothelial Cells in Comparison With Human Peritoneal and Omentum Membranes - Sharifiaghdas, Farzaneh; Hamzehiesfahani, Nahid; Moghadasali, Reza; Ghaemimanesh, Fatemeh; Baharvand, Hossein (Urology Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0;} @font-face {font-family:Tahoma; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:1627400839 -2147483648 8 0 66047 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} p.CharCharCharChar, li.CharCharCharChar, div.CharCharCharChar {mso-style-name:" Char Char Char Char"; mso-style-unhide:no; margin-top:0cm; margin-right:0cm; margin-bottom:8.0pt; margin-left:0cm; line-height:12.0pt; mso-line-height-rule:exactly; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Tahoma","sans-serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Introduction: For tissue engineering of the urinary tract system, cell culture requires to be established in vitro and an appropriate matrix acting as cell carrier should be developed. The aim of the present study was to assess the proliferation quality of mouse urothelial cells on 3 natural matrixes of human amniotic membrane (AM), peritoneum, and omentum, and to compare them with collagen matrix. Materials and Methods: Mouse urothelial cells were isolated by collagenase IV, and the urothelial cells (105 cells per milliliter) were cultured on the AM, peritoneum, omentum, and collagen. The pattern of growth and asymmetric unit membrane formation were analyzed by histologic examination and immunocytochemistry on the detached urothelium with pancytokeratin and uroplakin III, respectively. Electron micrographs were taken and cell layers, organelles, desmosomes, and junctions were studied. Results: Immunocytochemistry of cultivated cells confirmed the urothelial cells phenotype. Up to 4 cell layers were obtained on the AM and 1 to 2 layers on the peritoneum. Distribution of the urothelial cells on the omentum was not favorable, which was due to its large pores. Cell proliferation started later on the AM (7th day) compared to collagen (3rd day). Also, apoptosis started later on the AM (after 14 days) compared to collagen (7 days). Conclusion: These results showed that the AM can act as a cell carrier for culture of the urothelial cells, and its exceptional properties such as having various growth factors, availability, and cost-effectiveness make it a unique biological matrix for urothelial culture.